Psychometric properties of the world health organization quality of life instrument-abbreviated version in portuguese-speaking adults from three different countries - da Silva, Wanderson Roberto [UNESP]; Bonafé, Fernanda Salloume Sampaio [UNESP]; Marôco, João; Maloa, Benvindo Felismino Samuel; Campos, Juliana Alvares Duarte Bonini [UNESP] (FapUNIFESP (SciELO), 2018)
Objective: To evaluate the validity, reliability and invariance of the World Health Organization Quality of Life Instrument-Abbreviated version (WHOQOL-Bref) in Portuguese-speaking adults from three different countries. Methods: A total of 4,020 Brazilian, Portuguese, and Mozambican individuals participated in the study. The total sample was divided into four samples: Brazilian patients (n = 1,120), Brazilian students (n = 1,398), Portuguese students (n = 1,165) and Mozambican students (n = 337). Factorial validity of the WHOQOL-Bref was assessed by confirmatory factor analysis. The convergent and discriminant validities of the instrument were assessed using the average variance extracted (AVE) and the square of Pearson’s correlational coefficient (r2), respectively. Composite reliability and ordinal alpha were used as measures of reliability. The metric, scalar, and strict invariance of WHOQOL-Bref was evaluated by multi-group analysis in independent subsamples (within each sample) and only between Brazil and Portugal (transnational invariance), because the configural model of Mozambique was different. Results: The original model of the WHOQOL-Bref did not show a good fit for the samples. Different items were excluded to fit the instrument in each sample (different models for WHOQOL-Bref among Brazilian, Portuguese, and Mozambican samples). AVE and r2 were not adequate; however, the reliability of the WHOQOL-Bref was good, except in the Mozambican sample. Invariance was observed only in independent subsamples. Conclusion: The WHOQOL-Bref fitted models showed adequate factorial validity and invariance in independent subsamples. The transnational non-invariance of the WHOQOL-Bref shows the influence of culture on the operationalization of the quality of life construct.
Propriedades psicométricas do instrumento de qualidade de vida da organização mundial de saúde-versão abreviada em adultos falantes de língua portuguesa de três países diferentes
Keywords: Patients; Quality of life; Reliability; Students; Validity